2012
DOI: 10.1074/jbc.m112.378828
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of RNA Polymerase III Transcription from the Glycerol-repressed State

Abstract: Background: Maf1 is a global repressor of RNA polymerase (pol) III transcription whose function is phospho-regulated by nutrient and stress signaling pathways. Results: We tested the hypothesis that CK2 phosphorylation of Maf1 is required for derepression of pol III transcription. Conclusion:The hypothesis is not supported. Significance: CK2 regulation of pol III transcription is likely to involve targets other than Maf1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 35 publications
(89 reference statements)
2
17
0
1
Order By: Relevance
“…The results of several unbiased or Maf1-targeted phosphoproteomic studies [33,3538] combined with in vitro phosphorylation assays and functional studies of phosphosite and kinase/signaling mutants [3133,39] have found that the biologically important sites in yeast Maf1 are seven serine residues (amino acids 90, 101, 177–179, 209 and 210), six of which correspond to consensus PKA/Sch9 sites (RR/KXS/T)[40]. Phosphorylation of these sites changes the localization of Maf1 in the cell and alters the interaction of Maf1 with the polymerase [2933,41,42]. Mutagenesis studies indicate that no single phosphosite is critical, their contributions are cumulative and that residues 209 and 210 account for most of the phosphorylation on Maf1 [32].…”
Section: Targets For Regulation Of Pol III Transcriptionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results of several unbiased or Maf1-targeted phosphoproteomic studies [33,3538] combined with in vitro phosphorylation assays and functional studies of phosphosite and kinase/signaling mutants [3133,39] have found that the biologically important sites in yeast Maf1 are seven serine residues (amino acids 90, 101, 177–179, 209 and 210), six of which correspond to consensus PKA/Sch9 sites (RR/KXS/T)[40]. Phosphorylation of these sites changes the localization of Maf1 in the cell and alters the interaction of Maf1 with the polymerase [2933,41,42]. Mutagenesis studies indicate that no single phosphosite is critical, their contributions are cumulative and that residues 209 and 210 account for most of the phosphorylation on Maf1 [32].…”
Section: Targets For Regulation Of Pol III Transcriptionmentioning
confidence: 99%
“…Mutagenesis studies indicate that no single phosphosite is critical, their contributions are cumulative and that residues 209 and 210 account for most of the phosphorylation on Maf1 [32]. Indeed, recent experiments with an internally-deleted, functional MAF1 allele ( MAF1-id ) that is missing five of the seven phosphosites (noted above) suggest that phosphorylation of serines 209 and 210 is sufficient for the normal regulated localization of this protein [42]. Despite the fact that Maf1 is phosphorylated on many sites, the protein usually separates into just two species on high resolving one-dimensional SDS gels [29,30,32].…”
Section: Targets For Regulation Of Pol III Transcriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Caesin Kinase 2 (CK2) stimulates RNA pol III transcription via phosphorylation of TFIIIB (CK2 forms a stable complex with TFIIIB) and has also been reported to directly phosphorylate Maf1 in yeast and mammalian cell culture [35]. There are contradicting reports however on whether CK2 phosphorylation of Maf1 is required for derepression of RNA pol III transcription in yeast[35, 36] and a role for CK2 has yet to be investigated in other species. Taken together, phosphorylation clearly plays an important regulatory role in Maf1 function, but the details underlying this control need further refinement (Fig.…”
Section: Introductionmentioning
confidence: 99%